Acute Fatty Liver in Pregnancy: A Rare but Catastrophic Complication of Late Pregnancy - Nigar Sadaf; Rubina Hussain (ziauddin University, 2024)
ABSTRACT Acute fatty liver of pregnancy (AFLP) is a sudden catastrophic illness occurring almost exclusively in the third trimester, where microvesicular fatty infiltration results in encephalopathy and hepatic failure.1 Although the exact pathogenesis is unknown but the disease has been linked to an abnormality in fetal fatty acid metabolism. This abnormality is a deficiency in the LCHAD (long-chain 3-hydroxyacyl-coenzyme A dehydrogenase) enzyme. Clinical manifestation usually manifests in the third trimester (35 to 36 weeks of gestation) but some cases occur with a range of 28 to 40 weeks. The diagnosis of acute fatty liver of pregnancy is challenging task for clinician because of the nonspecific clinical presentation which may mimic conditions such as acute viral hepatitis, pre-eclampsia, HELLP syndrome. Ultrasound, CT, MRI may be used to diagnose this disease. Liver biopsy is the gold standard for the diagnosis of AFLP. The condition was previously thought to be universally fatal2 but aggressive treatment by stabilizing the mother with intravenous fluids and blood products in anticipation of early delivery has improved prognosis. Liver transplantation may be the option for severe liver failure patients. The mortality from AFLP is approximately 18% and deaths are usually secondary to sepsis, renal failure, circulatory collapse, pancreatitis or gastrointestinal bleeding. KEY WORDS: Fatty, Liver, Pregnancy.